Signaling versus costly information acquisition - Helmut Bester; Matthias Lang; Jianpei Li (Freie Universität Berlin, School of Business & Economics, 2018)
In Spence's (1973) signaling by education model and in many of its extensions, firms can only infer workers' productivities from their education choices. In reality, firms also use sophisticated pre-employment auditing to learn workers' productivities. We characterize the trade-offs between signaling by workers and costly information acquisition by firms. Information acquisition is always associated with (partial) pooling of worker types, and education is used as a signal only if relatively few workers have low productivity. Our analysis applies also to other signaling problems, e.g. the financial structure of firms, warranties, and initial public offerings.
urn:nbn:de:kobv:188-refubium-22546-7
Keywords: D82; D86; 330; Signaling; Information Acquisition; Auditing